Polemik di Seputar Hukum Isbat Nikah dalam Sistem Hukum Perkawinan Indonesia - Ramdani Wahyu Sururie (Al-Manahij: Jurnal Kajian Hukum Islam, 2017)
"Isbat nikah" is the verification of a marriage. Juridically, marriage verification is regulated under the laws such as Law No. 1 of 1974 on Marriage, Law Number 7 of 1989 on Religious Courts, and Law No. 3 of 2006 and Law Number 50 of 2009 on Changes in the Religious Courts Act. The regulations stipulate that marriage verification is allowed for marriage performed before the Law Number 1 of 1974. In practice, marriage verification submitted to the Religious Court is done after the enactment of Law Number 1 of 1974. The acceptance of "marriage verification" by the Religious Court for the marriage taken place after the 1974 Marriage Law was based on the Compilation of Islamic Law (KHI), whereas KHI's legal status is not included in the Indonesian legal order. The essence of marriage verification is a legal determination. This means that a verified marriage remains valid because the marriage that is verified is merely on administrative reason. The position of marriage verification is a part of giving legal protection and legal certainty. The position of the KHI, which regulates in more detail the marriage verification, functions regulatively in the midst of a vacuum of religious judicial law. In addition, the judge may decide whether to grant or deny the application of marriage verification. Thus, it can be concluded that the nature of marriage verification is a part of legal discretion.